System of rules integration problems and solutions to enterprise resource planing systems - Vasilecas, Olegas; Avdejenkov, Vladimir (Lietuvos matematikos rinkinys, 2021)
A Business rules (BR) and business rules engine (BRE) enables an organization to increase its agility and speed to adapt to business process changes. This article analyzes business rules, business rules engines, and possibilitiesof their applying in resourcesmanagement systems used by enterprises.Ways of implementing business rules are discussed, considering peculiarities of business resources engines. The analysis shows that one of the ways to employ business rules is databasemanagementwith the help of triggers. An analysis of business rules engines is performed, and an extension realizing business rules transformation intoDBMS triggers is suggested.
Keywords: business rules; business rules management systems; ERP systems